RESEARCH ON ENERGY CONSUMPTION IN GAS STORAGE IN UNDERGROUND STORAGE FACILITIES - Hrudz, V. Ya.; Sadlivskyy, V. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2025)
The problem of estimating energy costs during gas storage in underground gas storage facilities is considered. For this purpose, it is proposed to use the concept of the efficiency coefficient of an underground gas storage facility, which is determined by the ratio of useful work performed to the total amount of energy consumed. This approach will allow analyzing the ways of using energy resources in the process of gas storage, assessing the efficiency of energy resources use and outlining areas for their savings. The useful energy of gas, which must be stored in the productive horizon of an underground gas storage facility during its injection and long-term storage, should be considered the potential energy of gas in the formation, while the energy losses of gas during injection and withdrawal from the storage facility should be attributed to unprofitable energy losses. Using mathematical models of energy efficiency of gas in the reservoir during storage and wasteful energy consumption in the processes of its injection from the storage and subsequent withdrawal, an expression was obtained that links the value of the efficiency coefficient of the underground gas storage with the technological storage parameters, which are considered as the volume of active and buffer gas in the storage, maximum and minimum reservoir pressures, as well as the operating parameters of the booster compressor station, including the efficiency coefficient of gas compression. The result makes it possible to forecast energy consumption for gas storage in a specific gas storage facility if there is information about the real state of the equipment and communications and the parameters of the operation mode of the booster compressor station during injection. However, of greater interest is the analysis of the obtained dependence, thanks to which it is possible to outline the ways of operating the underground gas storage facility with the lowest energy costs. Based on the analysis, it was found that an increase in the relative volume of buffer gas leads to an increase in the storage efficiency, and an increase in the ratio of maximum and minimum reservoir pressures leads to its decrease, since with an increase in reservoir pressure, the duration of the compressor period for gas injection into the storage will increase, which will cause an increase in the volume of fuel gas for the compression process.